Evaluation of risk impact of consumers' behaviour in terms of exposure to Listeria monocytogenes in lettuce. (17th March 2014) - Doménech, Eva; Conchado, Andrea; Escriche, Isabel
Summary The influence that consumers have on the exposure assessment due to the presence of Listeria monocytogenes in lettuce was studied. Four stages of the food chain were considered: transport home, storage, handling and washing. A survey provided information about family behaviour classified as: one adult living alone (n = 77), one adult with children (n = 21), two adults (n = 75), two adults with children (n = 139) and seniors (n = 157). Multiple correspondence analyses revealed only slight differences between one adult living alone (with or without children) and the other groups. The simulation results highlighted that in all groups, 'transportation' and 'storage at home' did not increase contamination. In the 'handling' stage, Listeria was able to increase an average of 1 log CFU g−1, and in 'washing', consumers were able to reduce it to the values at retail. Finally, sensitivity analysis demonstrated that washing and surface contamination were the practices that had most influence on the risk.